Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/elan.200303015
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Adsorptive Stripping Voltammetry of Molybdenum: Redox Kinetic Measurements

Abstract: The electrode mechanism of Mo(VI) reduction was studied under catalytic adsorptive stripping mode by means of square-wave voltammetry (SWV). Mo(VI) creates a stable surface active complex with mandelic acid. The electrode reaction of Mo(VI)-mandelic acid system undergoes as one-electron reduction, exhibiting properties of a surface electrode process. In the presence of chlorate, bromate, and hydrogen peroxide, the electrode reaction is transposed into a catalytic mechanism. The experimental results are compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(28 reference statements)
2
5
0
Order By: Relevance
“…Previous studies have also shown that the catalytic term is faster for bromate than for chlorate for both Ti 41 and Mo. 42 Initial DP-CSV work showed that a combination of bromate and Cupferron was optimal, as high concentrations of Cupferron increased the blank considerably (see below). The presence of bromate (see Figure 3 and Figure S6 in the Supporting Information) lead to a characteristic positive wave immediately after the reduction wave of the TiO(Cup) 2 complex.…”
Section: Effect Of Varying the Adsorption Potential And Timesupporting
confidence: 52%
See 2 more Smart Citations
“…Previous studies have also shown that the catalytic term is faster for bromate than for chlorate for both Ti 41 and Mo. 42 Initial DP-CSV work showed that a combination of bromate and Cupferron was optimal, as high concentrations of Cupferron increased the blank considerably (see below). The presence of bromate (see Figure 3 and Figure S6 in the Supporting Information) lead to a characteristic positive wave immediately after the reduction wave of the TiO(Cup) 2 complex.…”
Section: Effect Of Varying the Adsorption Potential And Timesupporting
confidence: 52%
“…The presence of bromate (see Figure and Figure S6 in the Supporting Information) lead to a characteristic positive wave immediately after the reduction wave of the TiO(Cup) 2 complex. Such phenomena have also been observed in the catalytic adsorptive stripping of Mo . This change in peak shape was also responsible for an anodic shift in E p with the addition of bromate (Figure S7 in the Supporting Information), although further additions of bromate resulted in an increasingly cathodic shift, as also seen for bromate and Ti(EDTA) .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The presence of chlorate enhanced the reduction current which was attributed to the catalytic reduction of Mo(V) by chlorate. Chlorate as oxidizing agent convert probable Mo(IV) to Mo(V), whilst chlorate reduces to a metastable reduction product Cl(IV) 3740. This implies that the catalytic effect of chlorate enhances the sensitivity of the Cup‐SPCE toward Mo(VI).…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic electrode reactions are the focus of voltammetric analysis, as they provide a means for developing highly sensitive procedures for quantitative determination [1][2][3][4][5][6][7][8][9][10]. The simplest catalytic mechanism is an EC reaction scheme, where E refers to the electrode reaction and C is a follow-up irreversible chemical step with a first order kinetics, through which the electroactive reactant is regenerated.…”
Section: Introductionmentioning
confidence: 99%